CONTENTS (Medical Forum Monthly, 2024)
New Perspectives in the Management of Hypertension: Role of Herbal Medicines 3-7 Syed Mohsin Turab 2. Mahay Rookh 3. Amber 4. Usman Ghani Khan 5. Asif Bin Rehman 6. Shah Nawaz JamaliDetermination of Occlusal Vertical Dimension by Correlating Hand, Thumb and Index Finger Length with Craniofacial Measurements 8-11 Muhammad Irfan Majeed 2. Aaqil Malik 3. Muhammad AfzalClinical Evaluation of Coded Herbal Medicine (Hypoess) and Angiotensin Receptor Blocker (Candesartan) in Essential Hypertensive Patients 12-15 Shah Nawaz Jamali 2. Mahay Rookh 3. Amber 4. Usman Ghani Khan 5. Asif Bin Rehman 6. Syed Mohsin TurabReduction of Testicular Volume of Albino Rats in Lead Induced Toxicity and Reversal of IT with High Dosages of Vitamin C 16-20 Mujahid Akbar Mamoun 2. Syed Muhammad Tariq Ali Rizvi 3. Sajid Munir Qazi Influence of Oxidative Stress in Aging on Antioxidant Levels in Healthy Male and Females 21-23 Ishfaq Ali Shah Bukhari 2. Ikram Ullah 3. MusarratTo Asses the Knowledge of Women in Regards to Antenatal Care 24-27 Farhana Anjum 2. Nasreen Noor 3. Saeeda BanoTo Determine the Most Common Semen Abnormalities and Risk Factors Associated With Different Types of Semen Abnormalities in Infertile Male 28-32 Khawaja Fawad Parveiz 2. Shahzadi Saima Hussain 3. Rukhsana Karim 4. Simi Ghaffar 5. Shahbaz KhanBacteriological Profile and Antibiotic Susceptibility of Blood Isolates in Blood Stream Infections 33-36 Muhammad Usman Anjum 2. Nazia Shams 3. Syed Abir Hussain 4. Syed Humayun ShahFrequency and Sensitivity of Micro-Organism in Post-Operative Wound Infections: A Quest for Microbes 37-40 Arsala Aslam Pervaiz 2. Naeema Abdul Razzak 3. Adnan Aziz 4. Naheed SultanSurgical Fixation of Clavicular Fractures Outcome and Complications 41-43 Syed Qasim Mehmood 2. Asad Mehmood 3. Rifat Latif 4. Samson GriffinA Morphological Study of Atypical Uterine Bleeding 44-47 Niaz Mohammad 2. Chandi Kapoor 3. Amir Mohammad Babar 4. Samina TareenThe Impact of Training and Development on Employee’s Performance on Private and Public Hospitals in Lahore, Pakistan 48-52 Muhammad Usman Siddique 2. Attique-ur-Rehman 3. S. A. Jafri